Uncontrolled re-entries of spacecraft and rocket bodies: A statistical overview over the last decade. Issue 1 (March 2019) - Pardini, Carmen; Anselmo, Luciano
Highlights: The most critical historic re-entry events were reviewed. A statistical analysis of the uncontrolled re-entries of intact objects, from 2008 to 2017, was carried out. Spent upper stages accounted for nearly 82%, spacecraft for about 18%. The average re-entered mass was approximately 90 metric tons per year. In about 4% of the re-entries the casualty expectancy was expected to exceed the threshold of 10 −4 by almost one order of magnitude. Abstract: More than 24, 400 catalogued orbiting objects have re-entered so far into the Earth's atmosphere since the beginning of the space age. The associated returning mass, close to 30, 000 metric tons, was mainly concentrated in intact objects, i.e. payloads and spent upper stages, accounting for nearly 29% of the re-entered objects. During the 10 years from 2008 to 2017, almost 450 large intact objects have re-entered without control, with a total returning mass of approximately 900 metric tons. Since the beginning of 2018 until mid-November, nearly 86 metric tons of returned materials were associated with almost 65 uncontrolled re-entries of large intact objects, three of which with a mass exceeding 5 metric tons: the Zenit-3F second stage 2017-086D, the C-25 cryogenic upper stage 2017-031B, and the Chinese space station Tiangong-1. After an overview of the most critical historic re-entry events, the attention will be focused on the re-entries of massive objects occurred without control from 2008 to 2017, by categorizing them in terms of relevance, re-entry frequency, returned mass, distribution in inclination, overflown latitude bands, eccentricity and perigee/apogee altitudes before re-entry. Cases in which spacecraft and rocket bodies components were retrieved, and eyewitnesses sightings were reported, will be presented as well. Finally, the relevant re-entries occurred without control in 2018 will be discussed, while conclusions will be drawn concerning the potential growing risk on the ground and in mid-air due to fragments surviving the re-entry.